2001
DOI: 10.1128/aem.67.2.972-976.2001
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Ammonia-Oxidizing Bacteria in Arable Soil by Real-Time PCR

Abstract: Real-time PCR was used to quantify populations of ammonia-oxidizing bacteria representing the ␤ subdivision of the class Proteobacteria in samples of arable soil, both nitrogen fertilized and unfertilized, from Mellby, Sweden. Primers and probes targeting a 16S ribosomal DNA region of the ammonia-oxidizing bacteria were designed and used. In the fertilized soil there were ϳ6.2 ؋ 10 7 ammonia-oxidizing bacteria per g of soil, three times more than the number of bacteria in the unfertilized soil. The lytic effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
140
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(159 citation statements)
references
References 33 publications
15
140
2
Order By: Relevance
“…This is consistent with our observations; we observed a statistically significant effect only when both CO 2 and water were elevated. Several studies have also reported significant increases in AOB abundance in response to nitrogen fertilization (21,27,28), an effect we did not observe in our system. However, those studies were designed to mimic agricultural fertilization, with nitrogen applied at much higher rates than in our study.…”
Section: Resultscontrasting
confidence: 32%
“…This is consistent with our observations; we observed a statistically significant effect only when both CO 2 and water were elevated. Several studies have also reported significant increases in AOB abundance in response to nitrogen fertilization (21,27,28), an effect we did not observe in our system. However, those studies were designed to mimic agricultural fertilization, with nitrogen applied at much higher rates than in our study.…”
Section: Resultscontrasting
confidence: 32%
“…But, additional caution should accompany these results because the data were obtained from relatively few composite samples. Besides the DGGE bias already discussed, the impacts of DNA extraction and PCR amplification may have also contributed to further bias (20). Therefore, further research is needed to confirm the observations reported herein.…”
Section: Band Blast Search Acess Numbermentioning
confidence: 55%
“…Although sample enrichment does increase sensitivity, it essentially renders RT-PCR non-quantitative. RT-PCR has also been used to quantify ammonia-oxidizing bacteria in soil (Hermansson and Lindgren 2001), enterococci and human adenovirus in water (He and Jiang 2005), Vibrio vulnificus in shellfish and water (Panicker et al 2004), Lactobacillus salivarius in broiler chickens (Harrow et al 2007) and Clostridium tyrobutyricum in milk (López-Enríquez et al 2007).…”
Section: Microarraymentioning
confidence: 99%